Characterization of the Puumala orthohantavirus Strains in the Northwestern Region of the Republic of Tatarstan in Relation to the Clinical Manifestations in Hemorrhagic Fever With Renal Syndrome Patients - Davidyuk, Yuriy N.; Kabwe, Emmanuel; Shakirova, Venera G.; Martynova, Ekaterina V.; Ismagilova, Ruzilya K.; Khaertynova, Ilsiyar M.; Khaiboullina, Svetlana F.; Rizvanov, Albert A.; Morzunov, Sergey P. (Frontiers in Pharmacology, 2019)
Over 1000 cases of hemorrhagic fever with renal syndrome (HRFS) were recorded in the Republic of Tatarstan (RT) in 2015. HFRS is a zoonotic disease caused by several different Old World hantaviruses. In RT, Puumala orthohantavirus (PUUV) is a prevalent etiological agent of HFRS. We looked for the genetic link between the PUUV strains isolated from the bank voles and from the infected humans. In addition, possible correlation between the genetic makeup of the PUUV strain involved and different clinical picture of HFRS was investigated. Partial PUUV small (S) genome segment sequences were retrieved from 37 small animals captured in the northwestern region of RT in 2015. Phylogenetic analysis revealed that 34 PUUV sequences clustered with strains of the previously identified “Russia” (RUS) genetic lineage, whilst three remaining PUUV sequences clustered with the known lineage from Finland (FIN). Sequence comparisons showed that the majority of the S segment sequences isolated in the current study displayed 98.2-100.0% sequence identity when compared with the strains isolated earlier from the HFRS patients hospitalized in Kazan city. HFRS patients infected with PUUV strains of either RUS or FIN genetic lineages were observed to have consistent differences in clinical presentation of the disease and laboratory findings. These findings indicated a strong genetic link between the infected bank voles and human HFRS cases from the same localities. Thus, S segment sequences of the PUUV strains isolated from HFRS patients could serve as a molecular marker for determining the likely geographic area where infection occurred.